Strategi Branding Produk Lokal Wisata Halal di Aceh - Azman Sulaiman; Teuku Zulyadi; Fitrianti Fitrianti (Al-Idarah: Jurnal Manajemen dan Administrasi Islam, 2019)
Currently Indonesian government is working eagerly to improve the nation tourism industry, the focus is given especially to the local area of the country. Aceh province as one of the tourism destinations in Indonesia is also supporting the central government to achieve the goal which is improving the country`s tourism. In doing so, Aceh local government has undertaken several actions to manage, beautify and promote the industry in order to improve the local tourism sector. Besides the availability of tourism attractive activities, beautiful places and excellent services provided in the tourism destinations, the available of local products as tourist attraction is also a must- have in a tourist destination. Tourism industry is incomplete without the availability of local tourism products which has its own value to the visitor. Therefore, Aceh should produce and promotes a product that in-line with Islamic law (halal) because Aceh has been assigned as one province in Indonesia that offers Islamic tourism. This paper is studying the ability of the post- graduate students from Communication and Broadcasting Department (KPI) of UIN Ar- Raniry to conceptualize a branding strategy of Acehnese local products so that the products are attractive enough for tourists to buy it. The data is collected by doing field observation and interview with the producers of local tourism products.  FGD has been arranged to gain the students ‘thoughts on branding strategy concepts. The study shows that most of local tourism producers do not actively promote their products and FGD result offers several concepts of strategy branding that can be a reference for local producer in the future, they are: market survey, create a product, name a brand, packaging, promoting, marketing/ distributing and evaluating.